2003
DOI: 10.1111/j.1527-3458.2003.tb00248.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Properties of Spiradoline: A Potent and Selective k‐Opioid Receptor Agonist

Abstract: The selective ê-opioid receptor agonist spiradoline mesylate (U62,066E), an arylacetamide, was synthesized with the intention of creating an analgesic that, while still retaining its analgesic properties, would be devoid of the, mainly ì receptor mediated, side effects such as physical dependence and respiratory depression associated with morphine. Spiradoline is highly selective for the ê receptor with K i of 8.6 nM in guinea pig. Examination of the enantiomers of spiradoline, showed the (-)enantiomer to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 59 publications
2
102
0
2
Order By: Relevance
“…Activation of the κ-receptor produces severe, undesirable central nervous system side effects, which limit the clinical utility of κ-receptor agonists for pain relief [34,35] . In the present study, we found that the depression and sedation ED 50 values of MB-1C-OH are much higher than the ED 50 value for antinociception.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the κ-receptor produces severe, undesirable central nervous system side effects, which limit the clinical utility of κ-receptor agonists for pain relief [34,35] . In the present study, we found that the depression and sedation ED 50 values of MB-1C-OH are much higher than the ED 50 value for antinociception.…”
Section: Discussionmentioning
confidence: 99%
“…Spiradoline is highly selective for the kappa receptor and easily penetrates the blood brain barrier (Wadenberg, 2003). PL017 is an opioid agonist highly selective for mu receptors and produces long-lasting, naloxone-reversible analgesia in rats (Chang et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Ñïèðàäîëèí ïðîÿâèë ñåáÿ êàê âûñîêîñåëåêòèâíûé àãîíèñò k-ðåöåïòîðîâ (K i 8,4 nM) [62]. Íà ïîâåäåí÷å-ñêèõ ìîäåëÿõ íîöèöåïòèâíûõ ðåàêöèé â òåñòàõ "îò-äåðãèâàíèÿ õâîñòà", "ãîðÿ÷åé ïëàñòèíû", "óêñóñíûõ Õèìèêî-ôàðìàöåâòè÷åñêèé aeóðíàë.…”
Section: àãîíèñòû îïèîèäíûõ K-ðåöåïòîðîâunclassified
“…Ñïèðàäî-ëèí äîøåë äî ýòàïà êëèíè÷åñêèõ èñïûòàíèé, êîòîðûå âñêîðå áûëè ïðèîñòàíîâëåíû èç-çà âûðàaeåííîé ñåäà-öèè è äèñôîðèè [62,66]. Èññëåäîâàòåëè èç Êåìáðèäaeà [67,68] çàìåíèëè àðîìàòè÷åñêîå êîëüöî U50,488 íà áèöèêëè÷åñêóþ 10-p àðîìàòè÷åñêóþ ñèñòåìó, 4-áåíçîòèåíîâóþ èëè 4-áåíçîôóðàíîâóþ.…”
Section: òðàíñ-2-(34-äèõëîðôåíèë)-n-ìåòèë-n-unclassified